Information and the Formation of Inflation Expectations by Firms: Evidence from a Survey of Israeli Firms - Yuriy Gorodnichenko; Rafi Melnick; Ari Kutai (Institute of Labor Economics (IZA), 2023)
This study analyzes how firms form their inflation expectations during a regime change in monetary policy and a transition to a low-inflation environment. Using the Bank of Israel survey of firms, we document the basic properties of firms' inflation expectations and examine how Israeli firms update their inflation expectations after receiving new information about inflation or monetary policy. We find that even after successful de-dollarization and disinflation a positive inflation surprise leads to a sizable upward adjustment in inflation expectations for the next year and quarter. A surprise hike in the monetary interest rate leads to a downward adjustment in inflation expectations.
Keywords: D22; E31; E52; 330; monetary policy; surveys; firms; inflation expectations